O labirinto filosófico: recurso didático para uma educação menor no ensino de filosofia fundamental - Carlos, Daniel Moraes (Universidade Federal de São Carlos, 2025)
This dissertation, developed within the framework of the Professional Master’s Degree in Philosophy, proposes a pedagogical product aimed at teaching philosophy in Elementary Education (Cycles 1 and 2). The work is grounded in a central hypothesis: the teaching of philosophy should proceed from the child toward philosophy, rather than from philosophy toward the child. This reversal of perspective entails recognizing childhood not as an object of control or a stage to be overcome, but as a creative potency capable of operating and transforming thought. In this direction, the research articulates Sandra Mara Corazza’s critical genealogy of childhood with Gilles Deleuze’s philosophy of difference. From this dialogue emerges a pedagogical practice, inspired by Jacques Derrida, Silvio Gallo, and other authors, that breaks with the logic of explanation and the mere transmission of content and, from the perspective of “minor education,” seeks to resist both institutionalization and uncritical reproduction. The pedagogical dispositif developed—the “Philosophical Labyrinth”—materializes this hypothesis by catalyzing the Tragic Experience, understood not as suffering or catastrophe, but as a necessary condition for the emergence of autonomous thought and children’s philosophical authorship. Structured as a “workshop of concepts,” the dispositif fosters a collective, creative, and emancipatory philosophical practice that values the singularity of children’s thinking and experience as the foundations of philosophizing. Methodologically, the research adopts a qualitative and exploratory approach. The literature review is narrative in nature, selecting works that provide a foundation for understanding childhood and the right to philosophy, as well as the role of philosophy in Elementary Education. The documentary analysis focuses on UNESCO guidelines for the teaching of philosophy and the Municipal Curriculum of Indaiatuba (2022), confronting the required competencies with a proposal centered on conceptual creation. The ethnographic reflection procedure is configured as action research, in which the researcher, in his role as a teacher in the municipal school system of Indaiatuba, observes and records classroom dynamics, mapping “lines of flight” within the silences of children. The results indicate the viability of a philosophical practice that articulates children’s right to philosophy—recognized by UNESCO and the Convention on the Rights of the Child—with an approach that values “becoming-child” as a transgressive and ethical force. It is concluded that the teaching of philosophy in Elementary Education is genuinely philosophical only when it becomes a space of invention, resistance, and experimentation, capable of embracing childhood as an existential and political dimension, rather than merely as a developmental stage.
The philosophical labyrinth: a pedagogical resourse for minor education in the teaching of fundamental philosophy
Keywords: Ensino de Filosofia; Infância; Devir-criança; Educação menor; Experiência trágica; Labirinto filosófico; Philosophy Teaching; Childhood; Becoming-child; Minor Education; Tragic Experience; Philosophical Labyrinth; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::FILOSOFIA; 4. Educação de Qualidade